Obtaining AGNPS (silver nanoparticles) via green synthesis with marcella (achyrocline satureioides) extract, catalysis with microbial and antioxidant activity - Zalamea Molina, Luis Felipe; Chila Álvarez, Jenniffer Andreina; Menéndez Realpe, Irina Suley (Ingeniería Química y Desarrollo, 2022)
Green synthesis of NPs of silver, gold, copper, are a subject of investigative study that are currently carried out in India, Indonesia and Ecuador as is the case of this work from extract of Marcela (Achyrocline satureioides) and silver nitrate. The methodology used in obtaining NPsAg is via green synthesis that was performed with ionic reduction methods of the chemical components polyphenols and flavonoids such as: caffeic acid, galangin-3-methyl ether esters, quercetin; luteolin; 3-methoxy-quercetin and a new chalcone: achyrobichalcone. These methods of identification and characterization of the ionic organic components, UV-Vis spectrophotometry and SEM (electron scanning microscopy) were performed. The sizes of NPs that were found in their spherical shape, with a diameter of 10-15nm. The result obtained from the antimicrobial activity with the strains E. coli and S. auerus resulting in an inhibition halo of 3.00 to 3.098 and 3.12 to 2.05 respectively.
Keywords: Achyrocline satureioides; Silver nanoparticles; Reducing agent; Flavonoid